Role of TIR1/AFB family genes during grafting in Carya cathayensis - Mei, Jiaqi; Tang, Xiaoyu; Gu, Yujie; Lu, Huijie; Yang, Ying; Shen, Qinyuan; Yang, Lingwei; Li, Bei; Zuo, Jianfang; Singh, Vijay Pratap; Sharma, Anket; Yuan, Huwei; et al. (Frontiers in Plant Science, 2024)
Auxins play significant roles in plant growth and development. The transporter inhibitor response1/auxin signaling F-box (TIR1/AFB) gene family encodes the auxin receptor proteins and plays an essential role in auxin signaling pathway. Here, we identified and characterized TIR1/AFB family in Carya cathayensis (Cc) plants (named as CcTIR1/AFB). Seven CcTIR1/AFBs were identified and further confirmed by cloning. All proteins encoded by these genes conservatively contained two domains, the F-box and leucine-rich repeat (LRR) domains. The CcTIR1/AFBs were located in the nucleus. Phylogenetic analysis suggested that CcTIR1/AFBs were evenly scattered in four different subgroups. The cis-acting element analysis indicates that CcTIR1/AFBs might be activated by auxin. The spatial and temporal expression of CcTIR1/AFBs during the grafting suggested that both CcAFB1 and CcAFB2 in scions and CcAFB4 in the rootstocks were significantly upregulated at 3 days after grafting, which indicated the specialization of three CcAFBs during grafting. The Y2H assay indicated that three CcAFBs were capable of interacting with CcIAA16, CcIAA27b and CcIAA29a, among which CcAFB4 interacted strongly with CcIAA1 and CcIAA16. Our study provides not only the opportunity to understand the potential role of CcTIR1/AFBs but also special CcAFBs (CcAFB1 ,2 ,4) which are great aspect for further exploring the molecular mechanism during the grafting process.